Extended Round Robin Load Balancing in Cloud Computing (International Journal of Engineering and Computer Science, 2014)
Cloud computing is a new platform for the developers where they can store and use their contents but as this is a new area and it is expected that sooner it will become very popular among all developers and its users. So, to avoid clusters and waiting in queues a load balancing is required. Most of the researchers are already working on it and we have also tried to work on same area with the use of round robin scheduling technique for load balancing.